2021
DOI: 10.3389/fonc.2021.632364
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of LDH-A by Oxamate Enhances the Efficacy of Anti-PD-1 Treatment in an NSCLC Humanized Mouse Model

Abstract: Immunotherapy is a curable treatment for certain cancers, but it is still only effective in a small subset of patients, partly because of the lack of sufficient immune cells in the tumor. It is reported that targeted lactate dehydrogenase (LDH) to reduce lactic acid production can promote the infiltration and activity of immune cells and turn tumors into hot tumors. Therefore, we constructed a humanized mouse model to evaluate the efficacy of using classical LDH inhibitor oxamate and pembrolizumab alone or in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 40 publications
0
48
0
Order By: Relevance
“…As in COAD immunotherapy, the combined therapy of nivolumab/lpilimumab can effectively control the progression of microsatellite instability-high COAD (47); triptolide can suppress the infiltration of macrophages in the TME and participate in the regulation of tumor cell growth and apoptosis of COAD (48); romidepsin can promote the expression of PD-L1 in COAD, and change the state of anti-tumor immune responses in vivo (49). Recent studies showed that LDHA may be served as a therapeutic target of cancer immunotherapy (50,51). Oya et al (50) found that the function of LDHA was similar to PD-L1 in the immunotherapy of non-small cell lung cancer (NSCLC).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As in COAD immunotherapy, the combined therapy of nivolumab/lpilimumab can effectively control the progression of microsatellite instability-high COAD (47); triptolide can suppress the infiltration of macrophages in the TME and participate in the regulation of tumor cell growth and apoptosis of COAD (48); romidepsin can promote the expression of PD-L1 in COAD, and change the state of anti-tumor immune responses in vivo (49). Recent studies showed that LDHA may be served as a therapeutic target of cancer immunotherapy (50,51). Oya et al (50) found that the function of LDHA was similar to PD-L1 in the immunotherapy of non-small cell lung cancer (NSCLC).…”
Section: Discussionmentioning
confidence: 99%
“…The patients with high LDHA expression levels indicated the poor efficacy of nivolumab in the treatment of NSCLC, and had shorter OS and progression free survival (PFS). Meanhwile, Qiao et al (51) demonstrated that in the NSCLC humanized mouse model, the LDHA inhibitor Oxamate could addictively enhance the efficacy of pembrolizumab that is an anti-PD-1 immunotherapy agent. Furthermore, GO analysis revealed that LDHA expression was also correlated with the immune system process to a certain extent (Figure 4B), suggesting that LDHA, as a novel target, has great prospect in the field of tumor immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the role of oxamate alone or in combination with pembrolizumab in the treatment of NSCLC, a PBMC-humanized mouse model was established. This model showed, while oxamate or pembrolizumab alone delayed tumor growth, their combination to be more efficient ( 95 ) ( Figure 2A ). This study successfully used humanized mice to demonstrate that new combination therapies can improve responsiveness to immunotherapy.…”
Section: Humanized Mouse Models In Cancer Immunotherapy Researchmentioning
confidence: 95%
“…Importantly, when these lactate-targeting treatments did improve outcomes, multiple studies showed this to be a CTL-dependent effect and treatment with LDH shRNA synergized with PD-1 ICB yet failed to improve tumor outcomes in immunodeficient systems [ 157 ]. Supporting this notion, LDH inhibition controlled tumor growth in a preclinical humanized non-small cell lung cancer model in a CD8 + T cell dependent manner [ 160 ]. It was recently shown that preconditioning CTLs with LDH-A inhibition resulted in less terminally differentiated CTLs upon IL-2 treatment, while treatment with IL-21 did not alter cellular metabolism but did decrease transcription of LAG3, PD-1, and TIM3, leading to an overall increase in cell persistence, tumor control, and host survival [ 161 ].…”
Section: Introductionmentioning
confidence: 99%